THU0504 Clinical and Functional Outcomes in Patients with Polyarticular Juvenile Idiopathic Arthritis Following Treatment with Adalimumab. (9th June 2015) - Kingsbury, D.; Quartier, P.; Horneff, G.; Minden, K.; Toth, M.; Varothai, N.; Cardoso, A.; Kalabic, J.
Abstract : Background: The Juvenile Arthritis Disease Activity Score (JADAS) is increasingly accepted for defining a treat-to-target strategy in patients (pts) with juvenile idiopathic arthritis (JIA) 1 Objectives: To use JADAS to evaluate clinical disease activity/control, with or without functional control, in pts with polyarticular or polyarticular-course JIA (pJIA), following the initiation of adalimumab (ADA) ± concurrent methotrexate (MTX) treatment. To assess the feasibility of JADAS definition of remission (REM) and minimal disease activity (MDA) as part of a treat-to-target strategy. Methods: Data for this post hoc analysis originated from M10-444, an open-label study in pJIA pts 2 to <4 yrs old or ≥4 yrs weighing <15 kg with moderately to severely active pJIA, in the US and EU (in the EU pts had to previously fail, have an insufficient response, or intolerance to MTX). Pts received subcutaneous ADA (24 mg/m 2 body surface area, up to 20 mg/dose), every other week (wk), for ≥24 wks, or until pts reached 4 yrs and weight ≥15 kg (in the EU, pts could continue for up to 1 additional yr). Disease activity was determined by JADAS based on C-reactive protein (CRP, normalization from 0-10), for 10 or 27 joints (JADAS10/27); functional impairment was determined by the Disability Index- Childhood Health Assessment questionnaire (DI-CHAQ). At wks 12 and 24, the proportion of pts achieving physician-assessed REM (JADAS≤2) or MDA (JADAS≤3.8), and the proportion of pts who achieved both MDA/REM and DI-CHAQ<0.5, was determined using observed cases. Results: Out of 32 pts, 25 (78%) had received prior MTX and 27/32 (84%) received concomitant MTX during the study. At baseline, pts had a mean JADAS10 of 18.8, JADAS27 of 19.0, and DI-CHAQ of 1.2. After 12 wks on open-label ADA, improvements were observed in clinical and functional outcomes. At wks 12 and 24, the mean JADAS10 was 6.2 and 5.3; mean JADAS27 was 6.4 and 5.6; mean DI-CHAQ was 0.7 and 0.7, respectively. No pts were in REM/MDA at baseline; however after 12 and 24 wks, a sizeable proportion achieved disease control (table ). After 12 and 24 wks of ADA treatment, the proportions of pts achieving both, disease control and DI-CHAQ<0.5 also increased from baseline. Conclusions: Addition of open-label ADA treatment resulted in clinically important improvements in clinical and functional outcomes in pts with pJIA. JADAS 10 and -27 gave comparable results. JADAS REM and MDA are achievable targets with ADA treatment. References: Consolaro et al, Arth & Rheum. 2012. Acknowledgements: AbbVie sponsored the study, participated in the design, data collection, analysis, and interpretation; and in the writing of the final version. Medical writing support was provided by Naina Barretto, PhD, of AbbVie Disclosure of Interest: D. Kingsbury Grant/research support from: AbbVie, P. Quartier Grant/research support from: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, and Swedish Orphan Biovitrum, Consultant for: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, and Swedish Orphan Biovitrum, G. Horneff Grant/research support from: AbbVie, Pfizer, Roche, Speakers bureau: AbbVie, Novartis, Pfizer, and Roche, K. Minden Grant/research support from: Pfizer and Abbvie, Consultant for: Pfizer, Abbvie, Roche and Pharm-Allergan, M. Toth: None declared, N. Varothai Employee of: AbbVie, A. Cardoso Employee of: AbbVie, J. Kalabic Employee of: AbbVie